The Influence of Self-Efficacy on Metacognition Skills of High Grade Students - Duratun, Asri Dwi; Maryani, Ika (International Journal of Elementary Education, 2023)
Self-efficacy and metacognition skills are two essential variables in achieving learning goals. However, the correlation between the two variables has yet to be discovered. This study aims to analyze and describe the significant effect of self-efficacy on the metacognition skills of high-class elementary school students. A quantitative research method with an ex-post facto or causal-comparative approach was used in this study. The study population was 88 students, and the sample was 72 students. Data were collected using questionnaires and documentation studies. Data analysis techniques used descriptive statistics and simple linear regression. Based on the results of the analysis, it is obtained that the hypothesis test states that there is a positive and significant correlation between self-efficacy and metacognition skills in high-class elementary school students through the Pearson correlation test, a significance value of 0.00 is obtained, which means it is smaller than 0.05, namely 0.00 <0.05, with a positive correlation of 0.784. So that when viewed from the existing degree guidelines, the Pearson correlation is strongly correlated. The obtained value of 10.573 means more significant than the t table value of 1.66629, namely 10.573 > 1.66629, with the acquisition of the regression equation Y = 12.822 + 0.713, which implies that self-efficacy is positively correlated with students' metacognition skills. So self-efficacy affects metacognition skills.